Fulfillment of Constitutional Rights of Stunting Children in Pekalongan Regency - Khasna, Syarifa; Nafisah, Sakilatun (Asian Journal of Law and Humanity, 2024)
Children have right For live , grow and develop as befits humans in general with Fulfillment right Constitutional in children affected by stunting is not quite enough state/ government responsibility Because in accordance with Contents the mandate stated in Article 28B paragraph 2 of the 1945 Constitution of the Republic of Indonesia. Fulfillment right constitutional in children Stunting in society Subdistrict Palm Regency Pekalongan . Research objectives This is For know How fulfillment right constitutional in children Stunting in society Subdistrict Palm Regency Pekalongan and how consequence law fulfillment right constitutional in children Stunting in society Subdistrict Palm Regency Pekalongan . Research This use method study juridical empirical with review and analyze implementation law in society about fulfillment right constitutional Stunting and consequence the law . Research results This show that Fulfillment of Constitutional Rights of Stunting Children in Society Subdistrict Palm Regency Pekalongan in accordance with implementation Constitution Number 23 of 2002 concerning Child Protection Article 4 States that every child entitled For can live , grow , develop and participate in a way reasonable in accordance with dignity and honor humanity , as well as get protection , law Number 36 of 2009 concerning Health in Article 132 States that every child entitled to obtain service health base in accordance with need medically , not yet fulfilled , because right child constitutional in the form of the Right to live , grow , develop as well as right to obtain health , that in the Sub-district Community palm tree found Still There is significant stunting data in the Sub-district Community palm tree Regency Pekalongan . Based on the Stunting program in the District palm tree Stunting phenomenon has not fully fulfilled in matter education Because government village only one or two who want cooperate with Health Center Sugar palm.